Projective Geometry—((ARC-RATIO)).—S.B’s Theorems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Projective geometry we never measure anything as in Euclidean geometry ; instead , we relate one set ofpoints to another by a projectivity. Generally , Projective geometry is a part of education in generalmathematics like Differential equation , Operation research and Statistics , Dynamics , Statics etc .Furthermore, projective geometry is very much prerequisite for algebraic geometry , one of modern day’s most vigorous ,interesting and exciting branches of mathematics on which a lots of research works are due , to be completed .In this paper I have tried to express some new ideas in lucid manner which are logically logical with diagramsand easy for the student audiences.